Dynamics, games and science : International Conference and Advanced School Planet Earth, DGS II, Portugal, August 28-September 6, 2013 /: International Conference and Advanced School Planet Earth, DGS II, Portugal, August 28-September 6, 2013. ([2015]) - Unknown
No abstract available